Chylothorax Associated with Subcutaneous Cellulitis Caused by Chylous Fluid Leakage in a Dog - Vieira, Raphael Simões; Dantas Mota, Francisco Cláudio; Borin-Crivellenti, Sophia; Oblak, Michelle (Acta Scientiae Veterinariae, 2019)
Background: Chylothorax is the accumulation of lymphatic fluid associated with molecules coming from digestion process (chyle) in the thorax. In this case report, we describe a canine patient with chylothorax that presented with an unusual clinical presentation: subcutaneous swelling due to chylous fluid leakage through the thoracic inlet. Case: A 4 year-old spayed female canine, Giant Schnauzer, presented to the Ontario Veterinary College Health Sciences Centre for evaluation and treatment of bilateral subcutaneous masses and edema on the ventral thorax. The patient was originally evaluated by the primary care veterinarian and aspiration and cytology of the masses resulted in a large volume of fluid with low cellularity, lightly basophilic. Due to the appearance of the fluid, triglyceride levels were performed and was 7.95 mmol/L while the peripheral level was 0.5 mmol/L (ref: 0.2-1.3 mmol/L). Based on the cytology and triglyceride levels, chylous fluid was suspected to be the cause of the swelling and edema. Over the following 10 months, the swelling progressed to bilateral tumors of approximately 15 cm in the lateral thorax and surrounding edematous tissues on the ventral thorax. The patient was referred for evaluation. On presentation the patient was normal aside from the described thoracic swellings and decreased lung sounds on auscultation. Thoracic ultrasound revealed bilateral pleural effusion. Thoracentesis resulted in approximately 1,200 mL of chylous fluid. Thoracic computed tomography (CT) and lymphangiography through popliteal injection revealed bilaterally in the soft tissues of the axillary regions, and extending along the right thoracic wall, a moderate amount of fluid dense material. The lymphangiogram revealed two sites of rupture of lymphatic vessels, in the caudal thorax (right sided), and in the cranial mediastinum/right thoracic inlet. Based on the findings, a video-assisted thoracic duct ligation and cisterna chyli ablation were performed. A PleuralPort was placed at the time of surgery for percutaneous drainage of residual fluid. Initially the subcutaneous swelling/masses were noted to have resolved and the patient was discharge 3 days postoperatively with minimal residual thoracic fluid at the time of discharge. Five days after discharge, the patient was returned because the owners complained of not being able to perform the thoracic drainage through the PleuralPort. Based on the physical exam and radiography, the suspicion of PleuralPort obstruction or kink was raised. Thoracocentesis drained 2.5 L of apparently chylous fluid. On the next day, the patient returned for replacement of the port. Eighteen days after the replacement of the port, the patient presented again due to concerns about an inability to drain the pleural port, and that the patient respiration was becoming more laborious, especially during the night. Due to the continued presence of chylous effusion, the owners were offered a repeat lymphangiogram to determine whether additional unligated branches could be contributing to the continued effusion. The owners elected humane euthanasia. Discussion: Canine chylothorax with leakage of chylous fluid to the thoracic subcutaneous space has not been described until now. The fluid retrieved from the patient subcutaneous swellings was a chylous fluid, originated from the thorax. We hypothesized that the leakage of chylous fluid occurred through the thoracic inlet, where there is the pleural cupula, a protuberance of the pulmonary pleura, not protected by the ribs, place that could rupture easily. Because similar case was not reported, we found it important to be shared, so the veterinary scientific community can be aware of uncommon clinical presentations in patients with chylothorax.